Synthesis and Applications of Silyl 2‐Methylprop‐2‐ene‐1‐sulfinates in Preparative Silylation and GC‐Derivatization Reactions of Polyols and Carbohydrates. Issue 12 (11th February 2016) - Marković, Dean; Tchawou, Wandji Augustin; Novosjolova, Irina; Laclef, Sylvain; Stepanovs, Dmitrijs; Turks, Māris; Vogel, Pierre
Abstract: Trimethylsilyl, triethylsilyl, tert ‐butyldimethylsilyl, and triisopropylsilyl 2‐methylprop‐2‐ene‐1‐sulfinates were prepared through (CuOTf)2 ⋅C6 H6 ‐catalyzed sila‐ene reactions of the corresponding methallylsilanes with SO2 at 50 °C. Sterically hindered, epimerizable, and base‐sensitive alcohols gave the corresponding silyl ethers in high yields and purities at room temperature and under neutral conditions. As the byproducts of the silylation reaction (SO2 +isobutylene) are volatile, the workup was simplified to solvent evaporation. The developed method can be employed for the chemo‐ and regioselective semiprotection of polyols and glycosides and for the silylation of unstable aldols. The high reactivity of the developed reagents is shown by the synthesis of sterically hindered per‐ O ‐ tert ‐butyldimethylsilyl‐α‐d ‐glucopyranose, the X‐ray crystallographic analysis of which is the first for a per‐ O ‐silylated hexopyranose. The per‐ O ‐silylation of polyols, hydroxy carboxylic acids, and carbohydrates with trimethylsilyl 2‐methylprop‐2‐ene‐1‐sulfinate was coupled with the GC analysis of nonvolatile polyhydroxy compounds both qualitatively and quantitatively. Abstract : Regio‐ and chemoselective silylation of polyols and carbohydrates has been achieved by employing silyl sulfinates (see the picture; TBS= tert ‐butyldimethylsilyl, TES=triethylsilyl, TIPS=triisopropylsilyl, TMS=trimethylsilyl). The silylation reactions proceed in high yield because the reactions are mild and fast and produce only volatile byproducts. Furthermore, the silyl sulfinates are used as new derivatization reagents for the GC analysis of nonvolatile polyhydroxy compounds.